Perception and Knowledge about HIV/AIDS among Students in a Medical College in Western Nepal - Shankar, PR; Subish, P; Paudel, R; Alam, K (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Background : Medical students are taught about HIV/AIDS throughout the curriculum. The objectives of the present study were: a) To study the perceptions and knowledge of medical students regarding HIV/AIDS b) Obtain information on lacunae observed and. c) Compare the median scores among different subgroups Methods : The study was carried out among the first, third, (preclinical) and fifth and sixth semester (clinical) students at the Manipal College of Medical Sciences, Pokhara, Nepal. The students were explained the objective of the study and invited to participate. Written informed consent was obtained. Student perception regarding HIV/AIDS was studied by noting their degree of agreement with a set of 22 statements using a modified Likert-type scale. The median score was compared among different subgroups. Results : 163 students participated. The median score was 77 (maximum score 110). The median score was significantly higher among Nepalese students compared to other nationalities (p=0.000) and among the scholarship students compared to the self-financing (p=0.000). The free text comments stressed the importance of safe sex in controlling HIV/AIDS. Conclusion : The overall scores were high. The lacunae observed can be addressed through educational interventions. The foreign and the self-financing students need greater training to tackle HIV/AIDS. The study had many limitations which may affect its generalizability and representativeness and more detailed studies are required. Key words : HIV/AIDS, Knowledge, Medical students, Nepal, Perceptions DOI: 10.3126/saarctb.v6i2.3052 SAARC J. Tuber. Lung Dis. HIV/AIDS 2009 VI (2) 11-16